Mediating effects of generation Y work values’ in human resource practices and employee retention in Malaysia - Sarita Beram Shah @ Rajaram,; Mohamad Afzhan Khan Bin Mohamad Khalil,; Raemah Abdullah Hashim, (2019)
Employee retention has received much attention especially in Western world. However it has generated limited empirical research in Malaysia despite its perennial importance. Employee retention can improve the organisation’s competitive advantage which is currently one of the biggest challenges faced by organisations. Low employee retention or in other words, high employee turnover in Malaysia hovered around 16%from 2009 to 2016 and out of which, 78% of the total turnover was contributed by the manufacturing sector. The working environment in the manufacturing sector is generally more hazardous and strenuous in nature comparatively with other sectors. Additionally, Generation Y representing over 50% of the total work force and hold predominant role in the employment market in Malaysia are known to have different work values as compared to their predecessor generations thus making employee retention even more complex. Therefore, organisations should not structure a one-sizefit- all and generic employee retention practices. Instead careful planning and implementation of human resources practices will be required with the aim to retain Generation Y at their workplace. Moreover, it has been argued that monetary human resource practices i.e. compensation and pay is no longer sustainable and instrumental for employee retention. Hence, in this light, this study focuses on non-monetary human resource practices such career development, succession planning and work life balance to prove its 7 research hypotheses where there are other human resource practices beyond compensation which could retain employees. The Generation Y work values do have mediating effect in the relationship of the human resource practices and employee retention. Additionally, the population of this study will be individuals employed in the electrical and electronics manufacturing organisations and the sample size will be a minimum of 384. A mixed method research will be employed to integrate the quantitative and qualitative research with the aim of providing a more complete understanding of the research problem. (Abstract by authors)